Structural information aided automated test method for magic 4GL - Horváth, Ferenc; Gergely, Tamás (Acta Cybernetica, 2015)
Nowadays testing data intensive, GUI enhanced applications properly on an easily maintainable way has become a more crucial part of the application life cycle. There are many evolving technologies to support automatized GUI testing in various environments. However there are hardly any methods that support 4GLs, especially Magic. Fortunately, the characteristics of the 4th generation of programming languages - like explicit definition of the relations between GUI elements and data - eliminate most of the problems raised during testing the GUI in the case of 3GLs. By utilizing these advantages we were able to develop a generalized testing method that supports 4GLs, and as a proof of concept a system for testing Magic xpa applications was built. In this paper, a generalized testing method for 4GLs, our path and script generator algorithms, and their implementations for Magic xpa applications are presented. In addition, the cooperation of these components with existing solutions is demonstrated, and a test method that has been competed by the application of our tools (and which is an instantiation of the generalized method) is introduced as a possible use of the results.